Reflexivity in Two Zhuang Dialects1. (April 2017) - Schadler, Dagmar
Abstract: This paper provides a comparison of two closely related dialects of Zhuang that have two very different anaphoric systems. One of the dialects, Mashan Zhuang, allows locally bound pronouns and additionally employs a complex anaphor, whilst the other dialect, Qinzhou Zhuang, has only a bare self which licenses reflexivity across the board. A more detailed analysis of the internal DP structure shows that the distribution and the possibility of being able to act as a reflexive licenser of the various reflexive forms can be explained by differences in the necessity for having a filled FP layer. A closer look at possessive phrases provides further evidence for assuming two different structures for pronouns in these two dialects. Contrary to appearances, then, also the pronoun in Mashan Zhuang provides the complexity an element needs to act as a reflexive‐licenser.